Tendon Transfer Procedures for Correction of Foot Drop Due to Injury to the Peripheral Nerves or Muscles - Lauer, Henrik; Heinzel, Johannes Christoph; Vasselli, Benedetta; Farzaliyev, Farhad; Ritter, Jana; Kolbenschlag, Jonas; Daigeler, Adrien; Prahm, Cosima (Journal of Brachial Plexus and Peripheral Nerve Injury, 2025)
Background Foot drop is a challenging condition that significantly impacts the affected patient's mobility and quality of life. Tendon transfer has emerged as a viable treatment option. We hereby present data of the tendon transfer procedures in patients with foot drop in our department. Besides a detailed description of our surgical technique, we also compare our results with those reported in the literature.Methods Data from 17 patients (11 males and 6 females) suffering from foot drop due to peripheral nerve or muscle lesions were retrospectively analyzed. All the patients underwent tendon transfer procedures between 2017 and 2022. Assessed outcomes encompassed parameters such as strength of foot dorsiflexion, the necessity for postoperative orthotic devices, and patient satisfaction. Demographic data, the time elapsed from injury/illness to surgery, and the underlying causes of foot drop were collected.Results Postsurgery, 14 patients regained robust dorsiflexion strength (M4), while 2 exhibited slightly lower strength (M3) and 1 attained equal strength as on the unaffected side (M5). Corrective procedures were undertaken in five patients to address problems with tendon tension. After an average follow-up period of 11.9 months (± 9.13), 82.4% of patients reported a high level of satisfaction, although three patients experienced persistent foot inversion. Most patients (94.1%) no longer required orthotic devices following the operative procedure.Conclusion A tendon transfer procedure for correction of foot drop has proven to be a safe and effective treatment option, resulting in a high level of patient satisfaction and restoration of quality of life.
Keywords: foot drop; dorsiflexion; tendon transfer; peroneal nerve injury; tibialis posterior transfer